FROM THE CLASSROOM TO THE CATHEDRAL CHAPTER. RELATIVES, FRIENDS AND MASTERS IN THE ARCHBISHOP OF MEXICO. 1680-1730 (Tzintzun, Revista de Estudios Históricos, 2016)
Against the common opinion that it was the Spanish Crown and its advisors theones that named the clergy, the article examines the fact that this was not themonarch’s job, but on the contrary, it was the result of a very intricate process ofselection in which the Consejo de Indias, the Viceroy, the archbishops of the CathedralChapter participated making the decision. This way, when there were threecandidates, as in the contest of the canonship, one of them was pointed by the synodexaminer and the monarch usually chose him. However, the process had afundamental aspect: with a well paid, careful and diligent management, there wasa great possibility to obtain the benefice (canonry). This way rich families or powerfulclergymen related to wealthy corporations could access the position.
Keywords: Canonship; Cathedral Chapter; Archbischop of Mexico; clergy